Immediate Weight-Bearing and Range of Motion After Internal Fixation of Selected Malleolar Fractures: A Retrospective Controlled Study. Issue 6 (June 2021) - Fram, Brianna R.; Rogero, Ryan G.; Chang, Gerard; Krieg, James C.; Raikin, Steven M.
Abstract : Objectives: We studied the safety of immediate weight-bearing as tolerated (IWBAT) and immediate range of motion (IROM) after open reduction internal fixation (ORIF) of selected malleolar ankle fractures (defined as involving bony or ligamentous disruption of 2 or more of the malleoli or syndesmosis without articular comminution) and attempted to identify risk factors for complications. Design: Retrospective case–control study. Setting: Level 1 Urban Trauma Center and multiple community hospitals, orthopedic specialty hospitals, and outpatient surgicenters within one metropolitan area. Patients/Participants: Of 268 patients at our level 1 trauma center who underwent primary ORIF of a selected malleolar fracture from 2013 to 2018, we identified 133 (49.6%) who were selected for IWBAT and IROM. We used propensity score matching to identify 172 controls who were non–weight-bearing (NWB) and no range of motion for 6 weeks postoperatively. The groups did not differ significantly in age, body mass index, Charleston Comorbidity Index, smoking status, diabetes status, malleoli involved, percentages undergoing medial malleolus (60.9% IWBAT vs. 51.7% NWB), posterior malleolus (24.1% IWBAT, 26.7% NWB), or syndesmosis fixation (41.4% IWBAT, 42.4% NWB, P = 0.85). Intervention: IWBAT and IROM after ankle ORIF versus NWB for 6 weeks. Main Outcome Measurements: Postoperative complications, including delayed wound healing, superficial or deep infection, and loss of reduction. Results: There was no significant difference in total complications ( P = 0.41), nonoperative complications ( P = 0.53), or operative complications, including a loss of reduction ( P = 0.89). We did not identify any factors associated with an increased complication risk, including posterior malleolus or syndesmosis fixation, diabetes, age, or preinjury-assisted ambulation. Conclusions: We failed to demonstrate a difference in complications in general and loss of reduction in particular when allowing immediate weight-bearing/ROM in selected cases of operatively treated malleolar fractures, suggesting this may be safe. Future prospective randomized studies are necessary to determine if immediate weight-bearing/ROM is safe and whether it offers any benefits to patients with operatively treated malleolar fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.